Progress in biological chirality - Palyi, G. (Gyula), 1936-; Zucchi, C. (Claudia), 1964-; Caglioti, Luciano (Elsevier, 2004)
Following on from Advances in BioChirality, Progress in Biological Chirality provides a unique summary and review of the most recent developments in the field of biochirality. Living organisms use only one enantiomer of chiral molecules in the majority of biologically important processes. The exact origin and mechanisms for this surprising selectivity are not yet known. This book discusses current research aimed at identifying the scientific reasons that may contribute to this phenomenon. Progress in Biological Chirality takes an interdisciplinary approach to this exciting field, covering a wide range of topics, such as, theory, palaeontology and food technology, to name but a few. This book presents findings via a broad spectrum of scientific approaches making it an excellent overview of Biological Chirality, suitable for postgraduate students, practitioners and researchers in the field of chemistry, biochemistry, biology, palaeontology, and food science with an interest in Chirality. * This book contains 32 chapters written by Authors, who are leading authorities in the field * Presents the most recent research taking place in this highly challenging field * Contains both reference material for the specialist and provides an overview for those who are interested in the fundamental problems of biology and chemistry.